Social innovation for modified consumption by means of the school subject Art and crafts - Neuberg , Anita (FormAkademisk, 2021)
In this paper I will take a look at how one can facilitate the change in consumption through social innovation, based on the subject of art and design in Norwegian general education. This paper will give a presentation of books, featured relevant articles and formal documents put into context to identify different causal mechanisms around our consumption. The discussion will be anchored around the resources and condition that must be provided to achieve and identify opportunities for action under the subject of Art and crafts, a subject in Norwegian general education with designing at the core of the subject, ages 6–16. The question that this paper points toward is: How can we, based on the subject of Art and crafts in primary schools, facilitate the change in consumption through social innovation?